EFEKTIFITAS KONSEP DIVERSI DALAM PROSES PERADILAN ANAK PELAKU TINDAK PIDANA MENURUT UU NO. 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK (Dalam Proses Peradilan Anak Pelaku Tindak Pidana Di Kabupaten Malang) - Komariah, Komariah; Cahyani, Tinuk Dwi (Legality : Jurnal Ilmiah Hukum, 2016)
Enforcement of the Act No. 11 of 2012 on Juvenile Justice System provides protection of the rights of juvenile who commit criminal acts use the diversion approach to realize the concept of Restorative Justice. To figure out the implementation of the Act, it is necessary to study with the socio-legal research method in the Police District, the State Attorney and the District Court at Malang. The results of these studies found that the application of diversion has been effective although there are still some obstacles. One of the toughest obstacles to implementing a diversion to fit is the unavailability of places to educate, nurture and put the brat as stated in the law. The study also found that in Malang at least there are some organizations / institutions in applying the diversion of government supporters, among others: BAPAS and P2TP2A.